Rheb/mTORC1 Signaling Promotes Kidney Fibroblast Activation and Fibrosis - Jiang, Lei (American Society of Nephrology, 2013)
Ras homolog enriched in brain (Rheb) is a small GTPase that regulates cell growth, differentiation, and survival by upregulating mammalian target of rapamycin complex 1 (mTORC1) signaling. The role of Rheb/mTORC1 signaling in the activation of kidney fibroblasts and the development of kidney fibrosis remains largely unknown. In this study, we found that Rheb/mTORC1 signaling was activated in interstitial myofibroblasts from fibrotic kidneys. Treatment of rat kidney interstitial fibroblasts (NRK-49F cell line) with TGFβ1 also activated Rheb/mTORC1 signaling. Blocking Rheb/mTORC1 signaling with rapamycin or Rheb small interfering RNA abolished TGFβ1-induced fibroblast activation. In a transgenic mouse, ectopic expression of Rheb activated kidney fibroblasts. These Rheb transgenic mice exhibited increased activation of mTORC1 signaling in both kidney tubular and interstitial cells as well as progressive interstitial renal fibrosis; rapamycin inhibited these effects. Similarly, mice with fibroblast-specific deletion of Tsc1, a negative regulator of Rheb, exhibited activated mTORC1 signaling in kidney interstitial fibroblasts and increased renal fibrosis, both of which rapamycin abolished. Taken together, these results suggest that Rheb/mTORC1 signaling promotes the activation of kidney fibroblasts and contributes to the development of interstitial fibrosis, possibly providing a therapeutic target for progressive renal disease.